Properties of concrete containing recycled PET bottles as sand replacement - Misri, Zainora; Wan Ibrahim, Mohd Haziman; Abdul Awal, A.S.M (Penerbit UTHM, 2020)
The modern lifestyle along with the new technologies have contributed the increasing of waste materials production. Plastic is one of the waste materials which is non-disposal and non-biodegradable material that can remain on earth without degradation. The world produces nearly 150 million tonnes of plastics per year, which is nearly 4.8 tonnes per second and a per capita production of 25 kg/year [1]. The Malaysian Plastic Industry (2012), reported that Malaysia is one of the largest plastics producers in Asia [2]. In Malaysia, extensive consumption of PET bottle is one of the contribution to the increasing growth of plastic waste disposed in landfills. Reutilization of PET wastes in concrete technology is one of the innovative solution for reduce the materials cost and solve some of the plastics waste problems ..